(untitled) (Research, Society and Development, 2020)
Objective: The aim of the study was analyze nurses and nursing undergraduate students evaluation of the Massive Open Online Course (MOOC) Nursing Evaluation. Method: Exploratory research with a quantitative approach. The MOOC ‘Nursing Assessment’ addressed the topic of introduction to the Nursing process. The study population consisted of MOOC participants who took the course in the first edition from October 2016 to January 2017. After applying the inclusion and exclusion criteria, the final sample was composed of 118 participants. Data collection consisted of characterization data, presence perception through the Community of Inquiry Survey and two open questions. Results: The MOOC modality was not known by 62 (53%) of the participants and 69 (58.5%) had not previously taken this type of course. The course met the expectations of 94.9% of the participants. When comparing the average scores of the three dimensions of presence perception, there was a significant difference (p <0.001), with the presence of teaching being the dimension best evaluated. The lowest scores were concentrated on social presence. Conclusion: The teaching presence had the highest average score among the three presences evaluated, reflecting the quality of planning and the development of attractive and quality digital materials.